Attitudes and behaviour towards GM food - Spence, Alexa (2006)
The aim of this thesis was to examine attitudes towards genetically modified (GM) food and how these translate into behaviour. Research conducted divided quite neatly into two distinct sections. The first section explored explicit attitudes and other socio-cognitive constructs relating to behaviour towards GM food within the framework of different theoretical models including, most notably, the theory of planned behaviour (Ajzen, 1991). The second section measured implicit attitudes held towards GM food and the malleability of these attitudes, using an array of different reaction time tasks, e. g. the implicit association task (Greenwald, McGhee and Schwartz, 1998). A final experiment then linked these two sections by examining both implicit and explicit attitudes alongside various measures of behaviour in order to examine the predictive validity of these attitude constructs and how these may vary depending on the situation. Results indicated that socio-cognitive concepts of subjective norms, perceived behavioural control (PBC), self-identity and emotional involvement were useful alongside the construct of explicit attitudes in predicting intentions and behaviour towards GM food. In addition, measures of implicit attitude were found to be useful predictors of behaviour towards GM food, over and above explicit attitudes. Interestingly, measurementso f implicit attitude were found to be positive when measured in a context free manner but were also found to be malleable and differed considerably depending on the situational context of measurement. Actual behaviour was measured in a variety of different ways and these converged in demonstrating that the majority of participants would try GM food. Overall, findings indicated that within Britain more people than previously thought are likely to try GM food if it becomes more widely available.